2008
DOI: 10.1002/star.200800229
|View full text |Cite
|
Sign up to set email alerts
|

Granule Sizes of Canna (Canna edulis) Starches and their Reactivity Toward Hydration, Enzyme Hydrolysis and Chemical Substitution

Abstract: Granule Sizes of Canna (Canna edulis) Starches and their Reactivity Toward Hydration, Enzyme Hydrolysis and Chemical SubstitutionSmall and large granule fractions were isolated from canna starch (Canna edulis, green leaf cultivar), and their morphology, physicochemical properties, susceptibility towards granular starch hydrolyzing enzymes and chemical reaction with propylene oxide were investigated. Canna starch consisted of a mixed population of large, medium and small granules; the mean of granule diameter w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…As above described, starch sample (1 g) was accurately weighed and dispersed in 50 ml water. The pH was adjusted to the desired values (2,4,6,8,10, and 12) with 0.1 M HCl or NaOH. The slurry was allowed to stand at 30 ± 2 • C for 30 min and centrifuged (1870 × g, 30 min).…”
Section: Swelling Power and Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As above described, starch sample (1 g) was accurately weighed and dispersed in 50 ml water. The pH was adjusted to the desired values (2,4,6,8,10, and 12) with 0.1 M HCl or NaOH. The slurry was allowed to stand at 30 ± 2 • C for 30 min and centrifuged (1870 × g, 30 min).…”
Section: Swelling Power and Solubilitymentioning
confidence: 99%
“…However, investigations on this topic are very limited, and almost no work has been reported on the influence of HMT on this starch. [6][7][8][9][10] Therefore, such a study will be important to extensive utilization of C. edulis starch. In the present work, starch was extracted and purified from rhizomes of C. edulis, and then modified by HMT.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and physicochemical properties of starch are also closely related. Large starch granules tend to have higher total crystallinity and gelatinization peak temperature, while small starch granules tend to have lower water and chemical affinity and higher hydrolysis rate . Early‐flowering superior grains are significantly superior to late‐flowering inferior grains in terms of endogenous hormones and grain‐filling…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that starch composition (Amjad and William 1985), gelatinization and pasting properties (Eliasson and Karlsson 1983), enzymatic digestibility (Kasemwong et al 2008), baking characteristics (Lelievre et al 1987), crystallizing and swelling properties (Radosta et al 1992) are all affected by granule size and shape. Starch with predominantly B-type granules has been used as a fat substitute (Lim et al 2002), while starch with a high percentage of A-type granules has applications in the manufacture of biodegradable plastic film and carbonless copy paper (Nachtergaele and Van 1989).…”
mentioning
confidence: 99%